2D and 3D Models of Alzheimer’s Disease: Investigating Neuron-like Cells in Oxidative Environments - Salles, Geisa R.; Giraldi, Luiza A.; da Silva, Newton S. [UNESP]; Porcionatto, Marimelia A.; Pacheco-Soares, Cristina (American Chemical Society (ACS), 2025)
Alzheimer's disease (AD) is a complex and enigmatic neurodegenerative disorder in which amyloid-β (Aβ) aggregates and oxidative stress play crucial roles in neuronal damage. Aβ forms senile plaques, while reactive oxygen species (ROS)-induced oxidative stress causes cellular dysfunction. Elucidating neuronal injury led by mild and severe oxidative stress may provide insight into how neurons respond to toxic environments. In parallel, modeling AD three-dimensionally is in the spotlight, sustainably contributing to reducing animals in research and replicating spatially neuronal mechanisms, such as neurite network and oxidative stress responses. This study evaluates the effects of oxidative stress on neuron-like cells cultured in two-dimensional (2D) and 3D spheroids, strengthening their potential as platforms for AD investigation. For the 2D models, SH-SY5Y (cells from human neuroblastoma) cells were differentiated into the neuronal phenotype and exposed to mild or severe concentrations of oxygen peroxide (H2O2, 100 or 200 μM, respectively). Cytoviability, ROS, Aβ particle analyses, and morphological aspects were assessed. Neuronal cells under severe stress produced elevated levels of intra- and extracellular Aβ aggregates. A range of Aβ particle analyses were performed comparing their properties, and morphologically, neurites were compromised under severe stress. For the 3D models, SH-SY5Y spheroids were self-assembled by 10 days of cultivation on developed nonadhesive hydrogel microwells and differentiated into the neuronal phenotype; their area, circularity, and solidity were measured. Spheroids were exposed or not to 200 μM H2O2, stained for cytoskeleton/nuclei, and imaged by scanning electron microscopy (SEM), and their viability was evaluated. Throughout the cultivation period, spheroids grew and differentiated morphologically. Neurite distribution was observed along the 3D composition; however, under oxidative stress, cytoviability decreased, abnormal nuclear staining was observed surrounding the spheroids, and morphological disorganization was evident by SEM, representing structural disarrangement and nuclear disruption. Briefly, this study provides a basis for exploring oxidative stress and producing robust 3D approaches to unraveling AD mechanisms.